Doses de silício na produtividade e na indução de resistência de plantas de milho a Spodoptera frugiperda (smith) (lepidoptera: noctuidae) - Perdomo, David Nataren (2017)
Several authors have demonstrated that silicon (Si) confers resistance to plants against pests and diseases mechanically, by induction of production of chemical compounds or by attraction of third trophic level. This study evaluated Si induced resistance in maize plants against Spodoptera frugiperda (Smith) and the effect of this element on crop yield. The experiment was done in the agricultural year 2016-2017, in the Farm Capim Branco of Universidade Federal de Uberlândia and repeated twice (1st and 2nd harvests). The experimental randomized blocks as a 5x2 (0, 150, 300, 450, 600 kg Si ha-1 and with or without manual infestation with approximately 500 eggs of S. frugiperda per plant) factorial with four replications. Silicon was applied to the soil (calcium and magnesium silicate) one month before sowing the hybrid DEKALB 390RR2. Plant defoliation was evaluated with a visual scale at 29, 35, 40 and 45 days after emergence (pre-infestation evaluation, and evaluations 5, 10 and 15 days after manual infestation with S. frugiperda, respectively). Defoliation ratings were greater in plants manually infested with S. frugiperda for both growing seasons. Defoliation reduction with increasing soil Si dose was observed in the 1st harvest, adjusting a quadratic model. The trend of defoliation reduction started at Si dose of 450 kg ha-1, with minimum defoliation at 600 kg ha-1. In contrast, leaf silicon content increased linearly with increasing soil silicon doses in that same harvest. No effect of silicon on defoliation and no differences in silicon leaf content with increasing soil silicon doses were observed in the 2nd harvest. Greater corn kernel yield was observed in the 1st harvest (9,262.87 kg ha-1) than in the 2nd one (6,060.24 kg ha-1); however, no silicon effect was observed. Increased leaf Si content induced maize resistance against S. frugiperda; however, it did not affect corn yield.